2021
DOI: 10.1002/ccr3.4956
|View full text |Cite
|
Sign up to set email alerts
|

Sudden sensorineural hearing loss in a post‐COVID‐19 patient

Abstract: A detailed history and diagnostic evaluation for recent or past COVID‐19 infection is vital in patients presenting with Sudden Sensorineural Hearing Loss (SSNHL) since SSNHL could be a sequelae of COVID‐19 and timely diagnosis and intervention could significantly improve hearing and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Findings from the review reveal uncertainty and inconsistency regarding the underlying pathophysiology of the cochleovestibular symptoms in COVID-19 positive patients, with Pokharel et al ( 2021 ) maintaining that the absence of a clear pathophysiologic mechanism linking COVID-19 to SSNHL creates a vague association. Therefore, Koparal and Yılmazer’s ( 2021 ) recommended more research to examine the impact of COVID-19 on hearing, including the underlying pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings from the review reveal uncertainty and inconsistency regarding the underlying pathophysiology of the cochleovestibular symptoms in COVID-19 positive patients, with Pokharel et al ( 2021 ) maintaining that the absence of a clear pathophysiologic mechanism linking COVID-19 to SSNHL creates a vague association. Therefore, Koparal and Yılmazer’s ( 2021 ) recommended more research to examine the impact of COVID-19 on hearing, including the underlying pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
“…The reported rate of otological or vestibular symptoms varied significantly. For example, Korkmaz et al (2021) Ricciardiello et al (2021) reported that both ears can equally be affected, and the impairment could be unilateral or bilateral, and if bilateral, the symptoms can be symmetrical or nonsymmetrical (Karimi-Galougahi et al, 2020;Koparal & Yılmazer, 2021;Koumpa et al, 2020;Sriwijitalai & Wiwanitkit, 2020), with the severity of the hearing loss documented to range from mild loss to profound hearing loss (Beckers et al, 2021;Chern et al, 2021;Koparal & Yılmazer, 2021;Koumpa et al, 2020;Pokharel et al, 2021) and some evidence of puretone average being substantially worse in patients with COVID-19 when compared with healthy control groups, particularly in the high frequencies (Koparal & Yılmazer, 2021). Mustafa (2020) found that pure-tone hearing thresholds in high frequencies and amplitudes of transient evoked otoacoustic emissions (TEOAE) were significantly worse in this population, thus concluding that COVID-19 infection potentially has adverse effects on cochlear hair cell function even when infected individuals are asymptomatic for the cardinal disease symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations